A Juventude Negra Participa Descendo Até o Chão, Chão, Chão: Consciência Política ao Som do Bekoo das Pretas - Bezerra, Marcos Sales (2021)
The purpose of this dissertation is to analyze how the political consciousness and predisposition to political participation of a recent social category is configured: the black youth (black youth). The research sought to understand the importance of the noninstitutional political space, amid the sound of Saturday mornings, and the locus of the research was a cultural event, the Bekoo das Pretas, organized by the Instituto Das Pretas (IDP). We adopted the theoretical framework of Sandoval and Silva (2016) called "Analytical Model of Political Consciousness for the Understanding of Participation in Collective Actions". The qualitative research of exploratory descriptive nature carried out by case study, was carried out with 8 young black men between 15 and 29 years old who attend the event, being the Youth who participate (JP) and the Youth who do not participate (JNP) from other activism and/or social movements. The paths of data production carried out in the context of the pandemic of the new coronavirus (Covid-19) were: documentary research; autoethnography; field diary and interview with semistructured script. For analysis, the Content Analysis method was employed with a priori dimensions defined in the analytical model, as macro categories of analysis. The results reveal two configurations of consciousness: a) the youth of the laceration - the JNP, for being susceptible to changes and being involved in events that are inscribed in new market trends, always ready to be swept away; and b) the youth of tradition - the JP, for being linked to rites with more meanings of the past (memory of black culture) and strictly focused on the JN. The research allows us to point out that the Bekoo das Pretas constitutes itself as essential, by establishing in the JN the desire to move towards other political spaces and also to aim at being in other deliberative processes. A shared collective identity is revealed, among the JNP; and a collective identity under construction, of the JP, to the extent that the insertion in a new field (market) made by the IDP/Bekoo das Pretas, requires an inter-relationship with a new public (young non-blacks). This study contributed to explain realities where the panorama is universalized, and that to understand the social phenomena of these subjects, two or more theoretical frameworks would be adequate. It is concluded that this psychopolitical analysis made it possible to understand the youth situation of JN, in the context where the youth condition is universalized.